Dietary Whey Protein Decreases Food Intake and Body Fat in Rats - Zhou, June; Keenan, Michael J.; Losso, Jack N.; Raggio, Anne M.; Shen, Li; McCutcheon, Kathleen L.; Tulley, Richard T.; Blackman, Marc R.; Martin, Roy J. (Obesity (Silver Spring, Md.), 2011)
We investigated the effects of dietary whey protein on food intake, body fat, and body weight gain in rats. Adult (11–12 week) male Sprague‐Dawley rats were divided into three dietary treatment groups for a 10‐week study: control. Whey protein (HP‐W), or high‐protein content control (HP‐S). Albumin was used as the basic protein source for all three diets. HP‐W and HP‐S diets contained an additional 24% (wt/wt) whey or isoflavone‐free soy protein, respectively. Food intake, body weight, body fat, respiratory quotient (RQ), plasma cholecystokinin (CCK), glucagon like peptide‐1 (GLP‐1), peptide YY (PYY), and leptin were measured during and/or at the end of the study. The results showed that body fat and body weight gain were lower (P < 0.05) at the end of study in rats fed HP‐W or HP‐S vs. control diet. The cumulative food intake measured over the 10‐week study period was lower in the HP‐W vs. control and HP‐S groups (P < 0.01). Further, HP‐W fed rats exhibited lower N2 free RQ values than did control and HP‐S groups (P < 0.01). Plasma concentrations of total GLP‐1 were higher in HP‐W and HP‐S vs. control group (P < 0.05), whereas plasma CCK, PYY, and leptin did not differ among the three groups. In conclusion, although dietary HP‐W and HP‐S each decrease body fat accumulation and body weight gain, the mechanism(s) involved appear to be different. HP‐S fed rats exhibit increased fat oxidation, whereas HP‐W fed rats show decreased food intake and increased fat oxidation, which may contribute to the effects of whey protein on body fat.